Environmental geochemistry of heavy metals in the groundwater of coal mining areas: A case study in Dingji coal mine, Huainan Coalfield, China. Issue 3 (3rd July 2019) - Zhang, Shizhen; Liu, Guijian; Yuan, Zijiao
Abstract: To elucidate the environmental geochemistry characteristics of groundwater in Huainan Coalfield, the largest coalfield in southern China, 59 groundwater samples from 12 locations were collected and measured for 18 heavy metals (Li, V, Cu, Pb, Zn, Cd, Ni, Mn, Co, Cr, Fe, Ba, Al, Be, Ti, Sr, Mo, and As), pH, and 7 ions (K +, Na +, Ca 2+, Mg 2+, Cl –, SO4 2–, and HCO3 – ). The Fe and Mn contents of most water samples were within class III of the People's Republic of China Quality Standard for Groundwater. The Pb, Zn, Cd, Cr, Co, and Ba contents were assessed by the fuzzy mathematical method, and their levels in the groundwater were within class II. pH was negatively correlated with 11 heavy metals (Li, V, Cu, Pb, Zn, Cd, Ni, Mn, Cr, Ba, and Sr) and positively correlated with Al, Ti, and Co. The ranking of uptake rates affected by pH was Al > Ba > Ti > Si > Li > Mn. The Li content was correlated with six ions (Na +, Ca 2+, Mg 2+, Cl –, SO4 2–, and HCO3 – ), Sr was correlated with the first five ions, and Ba was correlated with the first four ions. Principal component analysis of V, As, Mn, Pb, Cd, Ni, Cr, Li, and Zn in the groundwater indicated that they derived from lixiviation of soil and rocks, precipitation, surface runoff, and surface pollution by heavy metals.